Maggot and probiotic feed supplementation on growth performance and intestinal microbiota in Anguilla bicolor bicolor - Sutrisno Sutrisno; Otie Dylan Soebhakti Hasan; Triyanto Triyanto; Putu Angga Wiradana; Putu Eka Sudaryatma (Indonesian Society of Scientific Aquaculture (ISSA), 2026)
The purpose of this study was to determine the effectiveness of probiotic and maggot flour supplementation on production performance, water quality, and eel gut microbiota. There were five treatment groups of maggot flour doses (0, 25, 50, 75, and 100%) each with three replications. The eel seeds used were three months old (average weight 6.11 ± 4.28 g, average length 14.3 ± 3.22 cm) as many as 15 fish/aquarium which were fed until full twice a day for 60 days. Growth performance measurements were carried out every two weeks and at the end of the study, survival rate, feed digestibility, water quality, and the abundance of water and eel gut bacteria. The growth rate of group P1 (0% maggot flour) of 1.222 ± 0.662 g/day was significantly higher (P≤0.05) than group P5 (100% maggot flour) of 0.223 ± 0.094 g/day. The best FCR value was shown by treatment P1 of 2.576 ± 0.598. The highest protein digestibility was shown by group P5 at 75.90%, while the lowest protein digestibility was shown by group P1 at 62.41%. Low digestible protein and high fecal protein were shown by group P5 of 15.15% and 28.77%, respectively. The abundance of bacteria in the Bacillus sp. and Lactobacillus sp. groups dominated in groups P2 and P5. Based on the research results, it can be concluded that the use of commercial probiotics and 100% dose of maggot flour is not yet effective in improving growth performance, but can increase the abundance of good bacteria in the intestines of eels. Keywords: Anguilla bicolor, growth parameters, gut microbiota, maggot flour, probiotic Abstrak Tujuan penelitian ini adalah untuk mengetahui efektivitas suplementasi probiotik dan tepung maggot terhadap performa produksi, kualitas air, dan mikrobiota usus sidat. Terdapat lima kelompok perlakuan dosis tepung maggot (0, 25, 50, 75, dan 100%) masing-masing dengan tiga kali ulangan. Benih sidat yang digunakan berumur tiga bulan (berat rata-rata 6.11 ± 4.28 g, panjang rata-rata 14.3 ± 3.22 cm) sebanyak 15 ekor/akuarium yang diberi pakan sampai kenyang sebanyak dua kali sehari selama 60 hari. Pengukuran performa pertumbuhan dilakukan setiap dua minggu sekali dan akhir penelitian, tingkat kelangsungan hidup, daya cerna pakan, kualitas air, serta kelimpahan air dan bakteri usus belut. Laju pertumbuhan kelompok P1 (0% tepung maggot) sebesar 1,222 ± 0,662 g/hari lebih tinggi secara signifikan (P≤0,05) dibandingkan kelompok P5 (100% tepung maggot) sebesar 0,223 ± 0,094 g/hari. Nilai FCR terbaik ditunjukkan oleh perlakuan P1 sebesar 2,576 ± 0,598. Daya cerna protein tertinggi ditunjukkan oleh kelompok P5 sebesar 75,90%, sedangkan daya cerna protein terendah ditunjukkan oleh kelompok P1 sebesar 62,41%. Protein cerna rendah dan protein feses tinggi ditunjukkan oleh kelompok P5 masing-masing sebesar 15,15% dan 28,77%. Kelimpahan bakteri pada kelompok Bacillus sp. dan Lactobacillus sp. mendominasi pada kelompok P2 dan P5. Berdasarkan hasil penelitian dapat disimpulkan bahwa penggunaan probiotik komersial dan tepung maggot dosis 100% belum efektif dalam meningkatkan kinerja pertumbuhan, tetapi mampu meningkatkan kelimpahan bakteri baik dalam usus dari ikan sidat. Kata kunci: Anguilla bicolor, mikrobiota usus, parameter pertumbuhan, probiotik, tepung maggot